Simvastatin Effects on Skeletal Muscle Using the Biodistribution of 99mTc Sestamibi - Rezende, Natania Carol Cavalcante; Guerra, Sâmea Costa Pinheiro; Fernandes, Tatiane Uetti Gomes; Almeida, Yngra Bastos Mesquita Minora de; Macedo, Robson; Azevedo, Ítalo Medeiros; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2015)
Objective: Examining the effects of simvastatin on skeletal muscles in an experimental model of abdominal sepsis in rats through the biodistribution of 99mTc-sestamibi. Methods: Wistar rats were randomly assigned to 2 groups: with abdominal sepsis (n = 12) and without sepsis (n = 12). Six animals with sepsis and 6 controls were injected with a daily dose of 5 mg/kg/day of simvastatin by gavage for 3 days before induction of peritonitis and 4 hours before surgical procedure. The others received 1ml of 0.9% saline solution orally. The animals were anesthetized with 20mg/kg of xylazine and 50mg/kg of ketamine i.p. Cecal ligation and puncture were performed by laparotomy. The rats were under observation for 24 hours and their survival time was recorded. The animals were re-anesthetized and 0.1 ml of 99mTc-sestamibi was administered by i.v. 30 minutes later,the thigh muscle was biopsied for percentage of radioactivity per gram of tissue (ATI%/g) determination, measured by the automatic gamma counter Wizard Counter, PerkinElmer,Finland. Results: ATI%/g of Tc99m-sestamibi was higher in muscle samples of groups treated with simvastatin sepsis ((1.82?0.21), compared with saline-treated (1.07?0.19) and control groups (1.18?0.31;1.26?0.24); this is a statistically significant difference (p<0.001). Conclusion: The data resulting from this study allows for concluding that the pre-treatment with simvastatin contributed to a biodistribution increase of 99mTc-sestamibi into the skeletal muscle in the abdominal sepsis model in rats.